2017
DOI: 10.18203/2394-6040.ijcmph20170279
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness towards dengue infection and its prevention: a cross sectional study from rural area of Tamil Nadu, India

Abstract: Background: Dengue infection transmitted by Aedes aegypti is endemic in India. Environmental changes and lack of awareness result in increase in transmission of dengue infection and rise in dengue outbreaks. The present study was conducted to determine the knowledge of dengue infection and practices towards dengue prevention among a rural population in Kancheepuram district of Tamil Nadu.Methods:The study was cross sectional study, conducted in Kadambadi village of Kanchipuram district, Tamil Nadu. The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
(6 reference statements)
5
19
0
Order By: Relevance
“…In the study conducted by Malhotra et al, 72.62% of the study population were aware about mosquitoes transmitting dengue while Chellaiyan et al had reported 89%. 8,9 The result of the present study was also in accordance with a study done in Thailand by Swaddiwudhipong et al 10 In our study, more than fifty percent (53.7%) of the study population had correctly responded to the symptoms of dengue infection. This result is significantly less when compared to the results of the study done by Gupta et al 11 in rural and slum areas of Delhi where 92% of the respondents correctly responded that dengue fever will result in fever followed by headache.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study conducted by Malhotra et al, 72.62% of the study population were aware about mosquitoes transmitting dengue while Chellaiyan et al had reported 89%. 8,9 The result of the present study was also in accordance with a study done in Thailand by Swaddiwudhipong et al 10 In our study, more than fifty percent (53.7%) of the study population had correctly responded to the symptoms of dengue infection. This result is significantly less when compared to the results of the study done by Gupta et al 11 in rural and slum areas of Delhi where 92% of the respondents correctly responded that dengue fever will result in fever followed by headache.…”
Section: Discussionsupporting
confidence: 92%
“…8 But, the results of the study were similar to that obtained by Chellaiyan et al conducted near Chennai where 93.7% of the study participants knew about dengue. 9 This could be due to the fact that because of frequent outbreaks of dengue in South India when compared to North India and also due to awareness campaigns carried out by the government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Chellaiyan et al stated that two thirds (63.4%) of their participants used mosquito coils as preventive measures against dengue fever, about 15% used mosquito nets, and up to one fourth (24.1%) did not use any protective techniques against the mosquito bites. 12 Malhotra et al reported similar results. They stated that the most common preventive methods used in India were liquid vaporizers, mosquito coils, and health education.…”
Section: Knowledge Awareness and Attitude Towards Dengue Fever Outbrmentioning
confidence: 70%
“…Similarly, Chellaiyan et al studied the knowledge about dengue fever among rural inhabitants in India via a cross sectional study. 12 Among the 224 interviewed participants, 94% reported they had heard about the disease. However, when asked about the details of the disease, only 50% could correctly identify the disease symptoms, 40% knew about the breeding and biting habits of the mosquito, and 89% knew that the Aedes mosquito is the transmitting mosquito.…”
Section: Knowledge Awareness and Attitude Towards Dengue Fever Outbrmentioning
confidence: 99%
See 1 more Smart Citation